2011
DOI: 10.1245/s10434-011-2079-3
|View full text |Cite
|
Sign up to set email alerts
|

Is One Benign Fine Needle Aspiration Enough?

Abstract: The overall false-negative rate of thyroid FNAs is 10.2%, which is reduced to 4.5% with a second benign FNA. Ninety percent of patients with a false-negative FNA had suspicious sonographic features. Reaspiration should be considered in patients with sonographically suspicious nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
3
33
0
1
Order By: Relevance
“…Calcifications and atypia have been found to be strongly associated with malignant thyroid nodules in most series. 4,7,10,13,22 Data regarding nodule size is conflicting. Some authors have shown that larger nodule size is suggestive of malignancy, whereas others have shown that benign nodules tend to grow larger than malignant ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcifications and atypia have been found to be strongly associated with malignant thyroid nodules in most series. 4,7,10,13,22 Data regarding nodule size is conflicting. Some authors have shown that larger nodule size is suggestive of malignancy, whereas others have shown that benign nodules tend to grow larger than malignant ones.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have shown that routine second opinion review of cytopathology results in a different diagnosis in over one-third of FNAs. 3,4 Several molecular markers have been investigated for distinguishing benign from malignant thyroid nodules with indeterminate cytology. 5 Recently, a commercially available DNA microarray-based genomic classifier assay was shown to diagnose malignancy of indeterminate thyroid nodules with a positive predictive value of 47 % and a negative predictive value of 93 %.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in another study including the rebiopsies of benign nodules with suspicious ultrasonographic features, in 17.4% of them, suspicious cytology was found (14). Therefore, in some studies, TFNAB is recommended for benign thyroid nodules in follow-up (15). We faced various limitations during our study.…”
Section: Discussionmentioning
confidence: 78%